Migration of gap-opening planets in 3D stellar-irradiated accretion disks - Chrenko, O.; Nesvorný, D. (Astronomy and astrophysics (Berlin), 2020)
Context. The origin of giant planets at moderate separations ≃1–10 au is still not fully understood because numerical studies of Type II migration in protoplanetary disks often predict a decay of the semi-major axis that is too fast. According to recent 2D simulations, inward migration of a gap-opening planet can be slowed down or even reversed if the outer gap edge becomes heated by irradiation from the central star, and puffed up. Aims. Here, we study how stellar irradiation reduces the disk-driven torque and affects migration in more realistic 3D disks. Methods. Using 3D hydrodynamic simulations with radiation transfer, we investigated the static torque acting on a single gap-opening planet embedded in a passively heated accretion disk. Results. Our simulations confirm that a temperature inversion is established at the irradiated outer gap edge and the local increase of the scale height reduces the magnitude of the negative outer Lindblad torque. However, the temperature excess is smaller than assumed in 2D simulations and the torque reduction only becomes prominent for specific parameters. For the viscosity α = 10 −3 , the total torque is reduced for planetary masses ranging from 0.1 to 0.7 Jupiter mass, with the strongest reduction being by a factor of − 0.17 (implying outward migration) for a Saturn-mass planet. For a Jupiter-mass planet, the torque reduction becomes stronger with increasing α (the torque is halved when α = 5 × 10 −3 ). Conclusions. We conclude that planets that open moderately wide and deep gaps are subject to the largest torque modifications and their Type II migration can be stalled due to gap edge illumination. We then argue that the torque reduction can help to stabilize the orbits of giant planets forming at ≳ 1 au.